Effect of selected mental training on archers performance - Singh, S. S.; Singh, L. R.; Devi, M. L.; Patir, K.; Devi, S. S.; Singh, N. D. (Annals of the Bhandarkar Oriental Research Institute, 2024)
Objective: The main objective of the study was to find out the effect of selected mental training onarchers performance.